Uganda Brief 2018 - The African Seed Access Index - Mabaya, Edward; Mugoya, Mainza; Mubangizi, Emmanuel; Ibyisintabyo, Chris (African Seed Access Index, 2018)
A competitive seed sector is key to ensuring timely availability of high quality seeds of improved, appropriate varieties at affordable prices to smallholder farmers in Uganda. This country brief summarizes the key findings of The African Seed Access Index (TASAI) study conducted to appraise the structure and economic performance of Uganda’s seed sector in 2017. With a focus on four grain and legume crops important to food security in Uganda — maize, beans, millet, and sorghum — the study evaluates the enabling environment for a vibrant formal seed sector. These four crops account for about 35% of arable land in Uganda (FAOSTAT, 2017). The study covers 20 indicators divided into the following categories: Research and Development, Industry Competitiveness, Seed Policy and Regulations, Institutional Support, and Service to Smallholder Farmers. Appendix 1 summarizes all 20 indicators and compares Uganda to 12 other countries where similar studies were conducted. TASAI seeks to encourage public policymakers and development agencies to create and maintain enabling environments that will accelerate the development of competitive formal seed systems serving smallholder farmers.